Factores maternos y nivel de información sobre lactancia en madres adolescentes. Hospital de Apoyo Chepén, 2010 - Abanto Lalopú, Liliana (2010)
This research is a descriptive correctional crosscut was made to teenage mothers who attended the maternity service and the Operating Unit's Child Support Hospital Chepén, in order to determine the relationship between maternal factors: age, educational attainment and occupation, the level of information about breastfe eding. The sample consisted of 120 adolescent mothers with children under 6 months, we used a survey on maternal factors and a test to measure the level of information about breastfeeding .. Statistical analysis of results was performed using the Gamma test reaching the following results: o Most of the mothers are teenagers (75.0 percent) belong to the stage of late adolescence, have secondary education level (70.8 percent) and were housewives (79.2 percent). o The level of information on breastfeeding was (56. 7 percent) with a good level of information, followed by regular reporting level (37.5 percent) or significant relationship was found between the factors age and education level and the level of information on breastfeeding (p <0.05). o No significant relationship was found between the variable occupation and level of information about breastfeeding.